Talent Management Framework in China Youth Travel Agency - Yafang, Wang; Saufi, Akhmad (Asian Journal of Applied Business and Management, 2024)
In the context of China’s rapidly changing market and evolving workforce demographics, talent management has become a key factor in organizational success, particularly within service-oriented industries like the China Youth Travel Agency (CYTA). This study aims to explore the role of a structured talent management framework in driving employee motivation at CYTA, focusing on four dimensions: Talent Acquisition, Talent Development, Talent Deployment, and Talent Retention. Utilizing a quantitative research design, data was collected from 287 CYTA employees through a structured survey and analyzed using Structural Equation Modeling (SEM) path analysis. The findings reveal that each dimension of talent management significantly enhances employee motivation, with Talent Development showing the strongest impact. This research contributes to the literature by demonstrating the importance of an integrated talent management approach in fostering a motivated and committed workforce, essential for sustaining CYTA’s competitive edge and adapting to the dynamic demands of the travel industry.